Vloga kakovostnih predšolskih programov pri zagotavljanju socialne vključenosti ogroženih otrok - Jager, Jerneja (Šolsko polje, 2013)
The paper discusses the provision of social inclusion of disadvantaged children. Based on a review of relevant literature, research, and other documents, we found that high-quality preschool programs and competent professionals, who are sensitive to issues of social inclusion, significantly contribute to ensure the social inclusion of disadvantaged children. We present some of the factors that are, in the context of pre-school programs, associated with the provision of social inclusion (respect for diversity, inclusion, equal opportunities, justice in education; child-centred and culturally, developmentally and individually appropriate practice). A review of competencies of graduates of Early Childhood Education study program (first level; all three Faculties of Education in Slovenia), which can be linked to the provision of social inclusion of disadvantaged children, was carried out. In conclusion, the need for continuing professional development and reflection, which both enable adaptation to changes, with which educators are facing, is emphasized.
Keywords: disadvantaged children; predšolska vzgoja; predšolski otroci; social inclusion; preschool programs; otroški vrtci; quality; socialna vključenost; predšolski programi; competence; kakovost; kompetence